Temporal and cross-national comparisons of young Africans' HIV-related narratives from five countries, 1997–2014. (August 2020) - Winskell, Kate; Sabben, Gaëlle; Singleton, Robyn; Bednarczyk, Robert A.; Tiendrébéogo, Georges; Nkambule-Vilakati, Siphiwe; Dia, Fatim Louise; Mbakwem, Benjamin; Stephenson, Rob
Abstract: Little is known about how young Africans have made sense of the dramatic ways in which the HIV epidemic has evolved, and how that sense-making varies across countries with different epidemiological and sociocultural profiles. Symbolic representations of HIV and people living with HIV influence prevention, stigma, treatment-seeking, and illness experience. We compared social representations of HIV among young people from Senegal, Burkina Faso, Nigeria (South-East), Kenya, and Swaziland between 1997 and 2014. From a pool of 32, 759 HIV-themed creative narratives contributed by 10–24 year-olds to scriptwriting competitions at eight time points (1997, 2000, 2002, 2005, 2008, 2011, 2013, and 2014), we randomly sampled 1937 narratives, stratified by author's sex, age, and rural/urban residence. We quantified components of each narrative and calculated descriptive statistics and adjusted odds ratios, controlling for year, country, and author demographics. From 2005 onwards, representations of death, treatment access, and hopefulness improved significantly. Representations of death reached their lowest point in 2013, while biomedical treatment and hope peaked in 2011 and 2008, respectively, then declined. Narratives increasingly focused on female protagonists. Nigerian texts had significantly higher odds of death and blame, and lower odds of hope. A focus on life post-infection and representations of support for characters living with HIV increased with country HIV prevalence. Narratives by older authors were less blaming and more hopeful, supportive, and prevention-focused. While aggregate social representations in the narratives from 2005 to 2008-11 reflect increased optimism fostered by access to antiretroviral therapy (ART), positive developments are not sustained at this level. Stigmatizing representations persist, particularly in Nigeria. The hope-promoting and stigma-reducing influence of the advent of ART access may have partially run its course by 2011/2013. However, significant temporal and cross-national differences point to opportunities to reframe HIV in more constructive ways and contribute to improved education, communication, and stigma-reduction efforts. Highlights: Quantitative analysis of stratified random sample of 1937 HIV-themed narratives. From 2005, representations of death, treatment access, and hopefulness improved. Anti-stigma influence of ART access may have partially run its course by 2011/2013. Nigerian texts had higher odds of death and blame, and lower odds of hope. Demonstrates value of innovative data sources & rigorous humanities-based research.